Planejamento de rede LTE utilizando aproximação híbrida de modelo empírico outdoor: medição e técnica de algoritmo genético - PINHEIRO, Márcio Rodrigues (2015)
Currently, it is visible the growing number of mobile communications networks in the telecommunications scenario. In order to supply the demands of the most demanding users of mobile services with data transmission rates increasing constantly are developed by companies linked to the telecommunications industry, new technologies to keep up with these demands. As 2G and 3G networks can no longer bear the demands of current users because they can not provide quality services to customers due to limitations of data transfer rate. It was then developed, the LTE system (Long Term Evolution), which has become one of the most promising solutions to meet the growing demand of the telecommunications sector. In the LTE system, also called 4G is implemented efficiently on the network, various simulation tools to cover prediction has been developed. Great efforts have been invested in the development of these tools, in order that the predicted values are the closest possible to reality, making it indispensable in planning the LTE network. In this context, this paper is intended to study and optimization of outdoor propagation loss models available in the literature, operating in the 2.6GHz frequency range, in order to provide a propagation loss prediction more accurate the study environment. Therefore, signal measurements campaigns were held in Bethlehem in order to compare how satisfactory are the adjustments of the models of propagation loss with the signal loss measured in realized routes. It was observed that in certain measurements, models of propagation loss, did not show similar curves to that measured on the routes taken, showing high prediction error. Thus, optimization technique was used for all prediction models based on a Genetic Algorithm (GA). Through this technique, it was possible to achieve a significant improvement of the models studied compared the losses encountered on the routes taken, thus contributing to more efficient planning for networks operating in the LTE 2.6GHz range.